Colombian Museum of Historical Memory (2012-2019) A place for memorial dialogue? (2019)
As from 2011, the Centro Nacional de Memoria Histórica (National Centre of Historical Memory) has become a location for the official enunciation of memory in Colombia, consolidating itself as an institutional space which fosters an extensive reconstruction of historical memory. However, the Victim's Law, which created this centre and commissioned it to create, design, and manage a museum of memory, did not envision an institutional support structure for the places dedicated to memory in the country. The changes in political administration have jeopardized its work, resulting in important drawbacks in terms of victim participation, visibilization, research orientation, and financing. Taking this into consideration, the aim of this paper is to reflect, from the process of the construction and management of the Colombian Historical Memory Museum (2012-2019), upon how the changes in government affected the way in which memory is constructed from institutional locations. The pertinence of this approach is that said institution will become the most important landmark of representation of the memories of the armed conflict. It is hoped that it will be a central reference, as a symbolic official location regarding what is constructed, narrated and disseminated as the collective memory of the armed conflict in Colombia.